Thiophosphate analogs of coenzyme A and its precursors: synthesis, stability, and biomimetic potential - Löcherer, Christian; Tosun, Elif; Backes, Hannah; Jäschke, Andres (Biomolecules, 2022)
Coenzyme A (CoA) is ubiquitous and essential for key cellular processes in any living organism. Primary degradation of CoA occurs by enzyme-mediated pyrophosphate hydrolysis intracellularly and extracellularly to form adenosine 3’,5’-diphosphate and 4’-phosphopantetheine (PPanSH). The latter can be recycled for intracellular synthesis of CoA. Impairments in the CoA biosynthetic pathway are linked to a severe form of neurodegeneration with brain iron accumulation for which no disease-modifying therapy is available. Currently, exogenous administration of PPanSH is examined as a therapeutic intervention. Here, we describe biosynthetic access to thiophosphate analogs of PPanSH, 3′-dephospho-CoA, and CoA. The stabilizing effect of thiophosphate modifications toward degradation by extracellular and peroxisomal enzymes was studied in vitro. Experiments in a CoA-deficient cell model suggest a biomimetic potential of the PPanSH thiophosphate analog PSPanSH (C1). According to our findings, the administration of PSPanSH may provide an alternative approach to support intracellular CoA-dependent pathways.
Gesehen am 13.09.2022